Effects of exergaming on hippocampal volume and brain‐derived neurotrophic factor levels in Parkinson's disease. (14th November 2021) - Schaeffer, Eva; Roeben, Benjamin; Granert, Oliver; Hanert, Annika; Liepelt‐Scarfone, Inga; Leks, Edyta; Otterbein, Sascha; Saraykin, Pavel; Busch, Jan‐Hinrich; Synofzik, Matthis; Stransky, Elke; Bartsch, Thorsten; et al.
Abstract: Background and objective: Cognitive impairment is among the most burdensome non‐motor symptoms in Parkinson's disease (PD) and has been associated with hippocampal atrophy. Exercise has been reported to enhance neuroplasticity in the hippocampus in correlation with an improvement of cognitive function. We present data from the Training‐PD study, which was designed to evaluate effects of an "" training protocol on neuronal plasticity in PD. Methods: We initiated a 6‐week exergaming training program, combining visually stimulating computer games with physical exercise in 17 PD patients and 18 matched healthy controls. Volumetric segmentation of hippocampal subfields on T1‐ and T2‐weighted magnetic resonance imaging and brain‐derived neurotrophic factor (BDNF) serum levels were analyzed before and after the training protocol. Results: The PD group showed a group‐dependent significant volume increase of the left hippocampal subfields CA1, CA4/dentate gyrus (DG) and subiculum after the 6‐week training protocol. The effect was most pronounced in the left DG of PD patients, who showed a significantly smaller percentage volume compared to healthy controls at baseline, but not at follow‐up. Both groups had a significant increase in serum BDNF levels after training. Conclusions: The results of the present study indicate that exergaming might be a suitable approach to induce hippocampal volume changes in PD patients. Further and larger studies are needed to verify our findings. Abstract : After a 6‐week "exergaming" training program, patients with Parkinson's disease (PD) showed a significant volume increase of the left hippocampal subfields compared to healthy controls. The effect was most pronounced in the left dentate gyrus. This study indicates that exergaming might be a suitable approach to induce hippocampal volume changes in PD patients.